11‐4: Ionization Electric‐Field Organic Material Deposition Method for Reducing Shadow‐Mask Effect. Issue 1 (28th June 2021) - Park, Heemin; Song, Seungyong; Lee, Duckjung; Park, Jungsun; Park, Yeongje; Park, Wonhyeok; Kim, Sangsoo; Chu, Hyeyong
Abstract : To make a full‐color high‐resolution organic light emitting diodes (OLEDs) device, it is necessary to reduce mask shadow effect. The ionization‐electric field organic material deposition was proposed as an advanced method of organic material thin film deposition to reduce mask shadow effect. The organic material was ionized by contact with tungsten (W) metal mesh in vacuum chamber to which the electric field was applied to induce the organic material to be incident vertically with to the substrate. As a result, mask shadow effect was reduced by electric field without changing OLEDs device characteristics.